2016
DOI: 10.1007/s10554-016-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular assessment at cardiac MRI: initial clinical experience utilizing an IS-SENSE reconstruction

Abstract: Cardiac MR is considered the gold standard in assessing RV function. The purpose of this study is to evaluate the clinical utility of an investigational iterative reconstruction algorithm in the quantitative assessment of RV function. This technique has the potential to improve the clinical utility of CMR in the evaluation of RV pathologies, particularly in patients with dyspnea, by shortening acquisition times without adversely influencing imaging performance. Segmented cine images were acquired on 9 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…However, most of researches focus on the left ventricle (LV) segmentation because the LV is the biggest chamber of heart [3][4][5]. Compared to the LV, the segmentation problems of RV get more and more attentions in recent years, along with the increasing cognition about the function of RV [6][7][8]. For instance, some cardiac diseases such as pulmonary hypertension, cardiomyopathy and dysplasia, are all related to the RV.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of researches focus on the left ventricle (LV) segmentation because the LV is the biggest chamber of heart [3][4][5]. Compared to the LV, the segmentation problems of RV get more and more attentions in recent years, along with the increasing cognition about the function of RV [6][7][8]. For instance, some cardiac diseases such as pulmonary hypertension, cardiomyopathy and dysplasia, are all related to the RV.…”
Section: Introductionmentioning
confidence: 99%
“…The segmented steady-state free precession cine is currently considered the gold-standard technique for the measure-ment of ventricular volumes, including in CHD patients [2,[15][16][17]. However, these trends must be balanced with the clinically relevant LOA demonstrated in the Bland-Altman plots, mainly regarding the relative bias of RVEF (−13.7; +9.3%), which was also the case in other studies evaluating CS cine for RV assessment in non-CHD populations, where the LOA was reported to be from −10.5 to +11.6% [5,10,18,19]. A more recent study also found a similar performance of a novel real-time steady-state free precession spiral sequence reconstructed using CS in a pediatric-only CHD population, but did not evaluate the regional wall-motion abnormalities or the depiction of tricuspid-regurgitation-related flow artifacts [19].…”
Section: Discussionmentioning
confidence: 92%
“…In related work, Bogachkov et al [37] used this technique for right ventricular assessment. A 3D-Dixon based method was developed for measuring epicardial and pericardial fat volumes [38].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%